Polymorphisms of KCNJ6 Gene and Their Correlation with Immune Indicators in Yaks (Bos grunniens) - Wenwen Ren; Xiaoming Ma; Daoning Yu; Xiaoyun Wu; Yongfu La; Xian Guo; Min Chu; Ping Yan; Xianyong Lan; Chunnian Liang (Biomolecules)
Yaks are crucial to local herders’ economy and agriculture. However, several diseases pose a significant threat to the health of yaks and cause substantial economic losses for herders. Therefore, studying the immune indicators and breeding of yaks has become an important task. This study aimed to investigate the association between single nucleotide polymorphisms (SNPs) of the G protein-activated inwardly rectifying K+ channel 2 (KCNJ6, GIRK2) gene and yak immune indicators, with the goal of identifying potential candidate molecular markers for yak breeding. In this study, we genotyped 192 healthy adult yaks and detected three SNPs (g163684421 C > T, g163688148 C > T, and g163690745 T > C) in the yak KCNJ6 gene. These SNPs were found to be distributed in the yak population. Subsequently, we performed a linkage disequilibrium analysis and found that the linkage disequilibrium levels of g163684421 C > T and g163690745 T > C were relatively high. Through a correlation analysis of yak KCNJ6 gene SNPs and immune indicators, we found that g163684421 C > T and g163690745 T > C were significantly associated with IgA, IgG, IgM, CRP, HP, IL-2, IL-4, IFN-γ, and TNF-α (p < 0.05), and the mutation of these SNPs leads to a decrease in yak immune indicators. On the other hand, g163688148 C > T was significantly associated with IgG, IL-4, IFN-γ, TNF-α, IgA, CRP, and HP (p < 0.05), and the mutation of this SNP leads to an increase in yak immune indicators. In conclusion, we identified SNPs associated with yak immune indicators and found that KCNJ6 gene polymorphisms can serve as candidate molecular markers for yak immune indicators. This study provides valuable genetic resources for marker-assisted selection in yak breeding. The results of this study are of great importance for the research on yak immune indicators and marker-assisted selection in yak breeding.